PENDUGAAN UMUR SIMPAN IKAN ASAP MENGGUNAKAN JENIS ASAP TEMPURUNG KELAPA DAN JENIS IKAN AIR TAWAR - Asep Dedy Sutrisno; Wildan Qoharisma Salam (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
The purpose of this research was to find out the shelf life of smoked fish produced from different types of freshwater fish, namely bawal fish, tawes fish and nilem fish using different types of coconut shell smoke, first grade liquid smoke, second grade liquid smoke and direct smoke.This research was conducted using Arrhenius Method on smoked fish using different coconut shell smoke and different freshwater fish species and stored at 25oC for 6 days. The responses in this research is organoleptic response (color, texture, flavour), microbiological response (Total Plate Count) and H2S test and Indol test. The method of this research consists of a preliminary research conducted to obtain a panelist acceptance limit on smoked fish products. The main research was conducted to find out the shelf life of smoked fish using different types of coconut shell smoke with different freshwater fish using microbial parameters also analyzed H2S test and Indol test to determine the overall quality degradation in smoked fish. Based on the parameters of total microbes treated using Arrhenius method, the shelf life of smoked fish was 5.75 days for bawal with garde 1 liquid smoke, 5.91 days for bawal with grade 2 liquid smoke and 3.97 days for bawal with smoke directly. For tawes with grade 1 liquid smoke that is 6.33 days, 3.90 days for tawes with grade 2 liquid smoke and 4.45 for tawes with direct smoke. Nilem fish with grade 1 liquid smoke is 5.72 days, 6.09 days for nilem with grade 2 liquid smoke and 4.25 day for nilem with direct smoke.